Cat of the century - Brown, Rita Mae.; Gellatly, Michael (New York : Bantam Books, 2010)
Using animal cunning and human canniness, Harry Harristeen and her menagerie of mystery solvers must sniff out the answers behind the disappearance of alumni association board member Mariah D'Angelo. Mariah's car is on campus, and Tucker has found human blood near the school's stables.
Keywords: Haristeen, Harry (Fictitious character) -- Fiction; Murphy, Mrs. (Fictitious character) -- Fiction; Women detectives -- Virginia -- Fiction; Women cat owners -- Fiction; Cats -- Fiction; Crozet (Va.) -- Fiction; Mystery fiction